SOSIALISASI PEMANFAATAN MACHINE LEARNING UNTUK SISTEM PREDIKSI DALAM KEHIDUPAN SEHARI-HARI PADA SMK RAFLESIA DEPOK - Nilovar Asyiah; Nurhasanah; Rahmawati (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
The development of artificial intelligence (AI) technology, particularly Machine Learning, has had a significant impact on various aspects of daily life, especially in predictive systems used in digital services, education, and industry. However, the understanding of vocational high school (SMK) students regarding the basic concepts and applications of Machine Learning remains relatively limited. This condition causes students to function primarily as technology users without a clear understanding of the underlying processes and the benefits generated.Therefore, this community service activity aims to socialize and introduce the utilization of Machine Learning for predictive systems in everyday life to students of SMK Raflesia Depok. The methods employed in this activity include a preparation stage, interactive material delivery, demonstrations of simple Machine Learning applications, as well as discussion and question-and-answer sessions. The materials were presented using easy-to-understand language and supported by contextual examples to match the level of comprehension of vocational high school students. The results of the activity indicate an increase in students’ understanding, interest, and enthusiasm toward the basic concepts of Machine Learning and its applications in predictive systems. Through this activity, students are expected to develop better technological literacy, analytical thinking skills, and readiness to face the rapid development of digital technology and the demands of the future workforce.